Correlation between body image perception and spinopelvic parameters in ankylosing spondylitis. (3rd September 2018) - Lee, Jung Sub; Shin, Jong Ki; Goh, Tae Sik
Abstract: Objective: To identify relationships between spinopelvic parameters and body image perception in ankylosing spondylitis (AS). Methods: The study and control groups comprised 107 AS patients (18 women and 89 men) and 40 controls. All underwent anteroposterior and lateral radiography of whole spine, including hip joints, and completed clinical questionnaires. The radiographic parameters examined were sagittal vertical axis, sacral slope, pelvic tilt, pelvic incidence, lumbar lordosis, thoracic kyphosis, spinosacral angle (SSA), and spinopelvic angle (SPA). The Trunk appearance scale (TAPS), and the Scoliosis Research Society 22 appearance questionnaire (SRSapp) were administered to evaluate body image perception. Results: The patient and control groups were found to differ significantly in terms of sagittal vertical axis, sacral slope, pelvic tilt, pelvic incidence, lumbar lordosis, SSA, and SPA. However, no significant intergroup difference was observed for thoracic kyphosis ( p  > .05). Correlation analysis revealed significant relationships between radiographic parameters and body image perception. Multiple regression analysis was performed to identify predictors of body image perception scores, and the results obtained revealed age, SSA, and SPA significantly predicted SRSapp scores and that age and SSA predicted TAPS scores. Conclusions: AS patients and normal controls were found to differ significantly in terms of sagittal spinopelvic parameters. Correlation analysis revealed significant relationships between radiographic parameters and body image perception. In particular, age, SSA, and SPA were found to be significant predictors of body image perception scores in AS patients.